Future Research Directions on the “Elusive” White Shark - Huveneers, Charlie; Apps, Kirin; Becerril-García, Edgar E.; Bruce, Barry; Butcher, Paul A.; Carlisle, Aaron B.; Chapple, Taylor K.; Christiansen, Heather M.; Cliff, Geremy; Curtis, Tobey H.; Daly-Engel, Toby S.; Dewar, Heidi; et al. (Frontiers in Marine Science, 2018)
White sharks, Carcharodon carcharias, are often described as elusive, with little information available due to the logistical difficulties of studying large marine predators that make long-distance migrations across ocean basins. Increased understanding of aggregation patterns, combined with recent advances in technology have, however, facilitated a new breadth of studies revealing fresh insights into the biology and ecology of white sharks. Although we may no longer be able to refer to the white shark as a little-known, elusive species, there remain numerous key questions that warrant investigation and research focus. Although white sharks have separate populations, they seemingly share similar biological and ecological traits across their global distribution. Yet, white shark’s behaviour and migratory patterns can widely differ, which makes formalising similarities across its distribution challenging. Prioritisation of research questions is important to maximise limited resources because white sharks are naturally low in abundance and play important regulatory roles in the ecosystem. Here, we consulted 43 white shark experts to identify these issues. The questions listed and developed here provide a global road map for future research on white sharks to advance progress towards key goals that are informed by the needs of the research community and resource managers.